Peri-operative protein or amino acid supplementation for total joint arthroplasty: a systematic review and meta-analysis - Yashar Khani; Ali Salmani; Mohammad Elahi; Iman Elahi Vahed; Elias Sadooghi Rad; Alireza Bahrami Samani; Shaghayegh Karami; Mohammad Nouroozi; Amir Mehrvar (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Osteoarthritis (OA) affects weight-bearing joints, such as hips and knees, and its prevalence is rising due to factors like obesity and aging. Muscle atrophy, exacerbated by aging and surgery, increases the risk of joint instability and falls. Orthopedic surgeons explore dietary interventions to counteract these effects, with protein supplementation (PS) showing promise. This systematic review and meta-analysis assessed the effectiveness of PS in arthroplasty patients, comparing findings with sports medicine and sarcopenia literature. Methods Following PRISMA guidelines, we searched PubMed, Web of Science, Scopus, and Embase (February 2025) for protein and amino acid supplementation studies in total knee or hip arthroplasty (TKA and THA) patients. The quality assessment used the Cochrane risk of bias and the Newcastle–Ottawa Scale. Meta-analysis calculated effect sizes for muscle atrophy and strength outcomes. Results Nineteen studies (903 patients) evaluated oral or intravenous protein/amino acid supplementation over a mean follow-up of 55.2 days. Essential amino acids (EAA) significantly reduced muscle atrophy in quadriceps femoris muscle mass (SMD: 0.69; 95% CI: 0.44 to 0.95) and hamstring muscle mass (SMD: 1.04; 95% CI: 0.52 to 1.55). However, effects on intramuscular adipose tissue (IMAT) and muscle thickness (MT) were inconsistent. Muscle strength outcomes varied, with no significant effect on quadriceps muscle strength (QMS) or handgrip strength (HGS). Intravenous amino acid infusion improved muscle protein synthesis and reduced perioperative blood loss. Conclusions Protein and amino acid supplementation can reduce muscle atrophy in hip or knee arthroplasty patients. While effects on muscle strength and function are mixed, intravenous supplementation offers benefits. Further standardized research is needed to confirm these findings. Trial registration PROSPERO registration code (CRD42024555899).